2020
DOI: 10.1186/s12913-020-05232-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the diabetes Canada guideline dissemination strategy on dispensed vascular protective medications for older patients in Ontario, Canada: a linked EMR and administrative data study

Abstract: Background: The 2013 Diabetes Canada guidelines recommended routinely using vascular protective medications for most patients with diabetes. These medications included statins and angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs). Antiplatelet agents were only recommended for secondary prevention of cardiovascular disease. Using Electronic Medical Record (EMR) data, we previously found that guideline dissemination efforts were not associated with an increase in the rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…More research has been reported about the impact of the publication of different clinical guidelines. 17,18 A study by Jang et al 19 is one of the few to evaluate the effects of nationwide PIM criteria on reducing PIM use in older persons in South Korea during 2013-2016. The authors used interrupted time series (ITS) analysis and found that the level of PIM prevalence decreased 0.49% at the patient level and 0.41% at the prescription level immediately after implementation of the drug utilization review (DUR), but that the trend in PIM use was unchanged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More research has been reported about the impact of the publication of different clinical guidelines. 17,18 A study by Jang et al 19 is one of the few to evaluate the effects of nationwide PIM criteria on reducing PIM use in older persons in South Korea during 2013-2016. The authors used interrupted time series (ITS) analysis and found that the level of PIM prevalence decreased 0.49% at the patient level and 0.41% at the prescription level immediately after implementation of the drug utilization review (DUR), but that the trend in PIM use was unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the trend changes in PIM use after implementation of PIM criteria at the national level. More research has been reported about the impact of the publication of different clinical guidelines 17,18 . A study by Jang et al 19 is one of the few to evaluate the effects of nationwide PIM criteria on reducing PIM use in older persons in South Korea during 2013‐2016.…”
Section: Introductionmentioning
confidence: 99%